How is responsible leadership related to the three-component model of organisational commitment?. Issue 5 (5th June 2020) - Haque, Amlan; Fernando, Mario; Caputi, Peter
Abstract : Purpose: The increasing number of corporate scandals and averseness to employee commitment have brought the concept of responsible leadership (RL) to the forefront of organisational studies. Many studies have found that leadership practice is an antecedent of employees' organisational commitment. However, little attention has been devoted to exploring the newly evolved RL for its impact on employee commitment. This study examines the influence of RL on the three-component model of organisational commitment. Design/methodology/approach: Applying the Social Identity Theory of Leadership (SITL), this study investigates the relationships between RL and the three-component model of organisational commitment. In particular, this study is framed to apply RL as a value-based leadership approach to examine its relationship on employees' three types of organisational commitment such as affective, continuance and normative commitment. A web-based self-administered survey was applied to collect data targeting a sample of 200 full-time Australian employees. Findings: The study results show that RL significantly effects all three components of organisational commitment. Both affective and normative commitments were significantly associated by RL compared to employees' continuance commitment. Originality/value: The paper extends the knowledge regarding newly evolved concept of RL which explains the significance of employee commitment and, further it provides empirical evidence from the perspective of SITL. The main contribution in this paper comes from new knowledge about the associations among RL and the three-component model of organisational commitment.